Asia-Pacific sustainable development goals outlook. (Asian Development Bank, 2017)
This report examines each of the 17 Sustainable Development Goals (SDGs) and describes the outlook for achieving each one in the Asia-Pacific region. It singles out bright spots and hot spots, provides insights about each goal and points to emerging issues and reveals many of the common challenges that governments will confront as they work to develop appropriate responses to the 2030 Agenda for Sustainable Development. It represents a preliminary but comprehensive stocktaking effort in the region to provide the best available knowledge that can help governments, regional agencies and other development actors as they forge the much-needed social and political consensus on the gaps and priorities for achieving each SDG.